FROM VISION TO PRACTICE: A COMPREHENSIVE EVALUATION OF THE IMPLEMENTATION OF THE INDEPENDENT CURRICULUM WITH THE CIPP MODEL - Ihsan, Ihsan; Vinayastri, Amelia; Ernawati, Ernawati; Ghani, Abdul Rahman A. (World Psychology, 2024)
The Merdeka Curriculum, introduced by the Ministry of Education and Culture, aims to address learning loss stemming from the Covid-19 pandemic by emphasizing flexible learning, community involvement, and holistic student development. This study evaluates the implementation of the Merdeka Curriculum at Muhammadiyah High School 11 in Jakarta, utilizing the CIPP (Context, Input, Process, Product) model. Data were collected through structured interviews, observations, and documentation from the principal, vice-principal, teachers, students, and support staff. The findings demonstrate that the school is substantially engaged with the community (Context: score 3), the curriculum implementation is highly relevant (Input: score 4), human resources are well-prepared (Input: score 4), infrastructure necessitates technological upgrades (Process: score 3), and project-based learning effectively enhances student competencies (Process: score 3). Achievements concerning the Pancasila Student Profile indicate positive outcomes (Product: score 4). This study provides critical insights for educators and policymakers in curriculum development.